The Viking way: magic and mind in Late Iron Age Scandinavia - Price, Neil (Oxbow Books, 2019)
Magic, sorcery and witchcraft are among the most common themes of the great medieval Icelandic sagas and poems, the problematic yet vital sources that provide our primary textual evidence for the Viking Age that they claim to describe. Yet despite the consistency of this picture, surprisingly little archaeological or historical research has been done to explore what this may really have meant to the men and women of the time. This book examines the evidence for Old Norse sorcery, looking at its meaning and function, practice and practitioners, and the complicated constructions of gender and sexual identity with which these were underpinned. Combining strong elements of eroticism and aggression, sorcery appears as a fundamental domain of women's power, linking them with the gods, the dead and the future. Their battle spells and combat rituals complement the men's physical acts of fighting, in a supernatural empowerment of the Viking way of life. What emerges is a fundamentally new image of the world in which the Vikings understood themselves to move, in which magic and its implications permeated every aspect of a society permanently geared for war